IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL DENGAN MEDIA INTERNET UNTUK MENINGKATKAN KEMAMPUAN MENULIS BIOGRAFI SISWA SMA - Haryanti, Endang (Universitas Tanjungpura, 2018)
AbstractThis research aimed to provide direction and efforts which was done by teacher in implementing contextual learning model with internet media in improving writing skill of students of Class X MIPA 2 in writing text of figure biography. This study used classroom action research as a method in which referred to what the teacher did in order to improve the teaching learning process. The subject of this research was 37 students in class X MIPA 2 of SMA Negeri 8 Pontianak. The researcher used observation guidelines, written test, and document as the tools of data collection. The implementation of the contextual learning model was successfully improved the students’ writing skill on the text of figure biography. In the first cycle, the mean score of the students in writing the text of figure biography was 71.35. The completeness reached 70.27%, moreover the expectation of classical completeness was 75% with 75 for KKM. In the second cycle, the students’ mean score in writing the text of figure biography was 74.86. The completeness was reached 78.38%, meanwhile the expectation of classical completeness was 80% with 75 for the KKM. Furthermore, in the third cycle the mean score of the students in writing the text of figure biography was 83.24. The completeness reached 83.51%, while the expectation of classical completeness was 85% with 75 for the KKM. Keywords: implementation of contextual learning, internet, writing skill, biography